Pseudo-conditionals and causal assertibles in Stoic logic - Miguel López-Astorga (Principia: An International Journal of Epistemology, 2016)
The Stoics not only analyzed sentences showing to be clear conditionals. They also reviewed other kinds of sentences related to the conditional that are not exactly conditionals, for example, the pseudo-conditionals and the causal assertibles. In this paper, I try to argue that the Stoic account of such sentences reveals that certain problematic issues that contemporary cognitive science is concerned with, such as the ways the conditionals can be expressed or the pragmatic phenomenon of the conditional perfection, were already studied by the Stoics, and that they even gave their solutions to those problems. To do that, I resort to the semantic analysis of models usually made by the mental models theory, and use it as a methodological tool.